The DOES ENTERPRISE RISK MANAGEMENT DISCLOSURE MODERATE THE EFFECT OF CAPITAL STRUCTURE ON THE COMPANY VALUE? - dody hapsoro; lu’lu’ul jannah (Jurnal Ilmiah Ekonomi Dan Bisnis, 2020)
This study aims to examine the ability of corporate risk management disclosures to moderate the effect of capital structure on firm value. The population in this study is all companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with the criteria of non-financial companies that disclose enterprise risk management disclosure in 2018. The number of companies that meet the sample criteria is 386. The measurement of enterprise risk management disclosure uses checklists developed based on ISO 31000: 2009. An assessment of the extent of disclosure is made using content analysis methods. The independent variables in this research are capital structure, dependent variable is company value, and moderation variable is enterprise risk management disclosure. Data analysis using Partial Least Square (PLS) with Warp PLS 4.0 application. The result of research shows that capital structure has a positive and significant effect on company value. Enterprise risk management disclosure proved to moderate the effect of capital structure on company value.